Front Pages IJReSES Vol. 13, No. 1(2016) - Editorial Journal (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2016)
Front Pages IJReSES Vol. 13, No. 1(2016) *Note: This cover is a revision version of the Editorial Committee Preface section cover that was uploaded on May 26, 2017